Os sentidos da formação nas políticas de currículo em gestão ambiental - Souza, John Kennedy Azevedo (2019)
The senses of training in curriculum policies in Environmental Management is the object of this research. It is the analysis of the utterances, said and unsaid, regarding the professional formation in technological undergraduate level in Environmental Management in the State of Sergipe. The analysis of the research focused on the course pedagogical project of the Estácio de Sá University (UNESA / SE). The adopted methodology encompassed the analytical based documentary research and the objective hermeneutics of Ulrich Ôvermamn. The procedures of analysis of the documentary research were concentrated around the context of origin of the course offer, nature of the text, key concepts and internal logic of the text contained in the pedagogical project of the course. The categories of analysis were defined from record units and context units, considering the said and the unsaid regarding the meanings attributed to the professional training in environmental management in the analyzed documents. The obtained results point to three different senses of the professional formation of the environmental manager: (a) directions of formation (focused on the description of the profession); (b) directions in training (focused on prescription during training); (c) directions for training (aimed at the regulation of the profession, initial post-training). It was concluded that the directions of environmental management training: (1) are formed by theoretical knowledge (what to know: theories, authors and concepts) that require contextualization due to mastery and epistemological updating (observance of the origins and development of products, instruments and processes belonging to a particular area or branch of knowledge); (2) are focused on the acquisition of technical skills (what to develop: core skills required), highlighting the explicit convergence to the market, competitiveness and control over the intellectual products of the area (opinions, reports, models, etc.); (3) model professional action (how to do: working techniques and tools) based on systematic control over the processes and products of the work; (4) have a descriptive, prescriptive and regulatory dimension aiming to, respectively, (i) produce demonstrative effects of the profession (during training), when it brings up value judgment elements on training (and during training) aiming the control of the profession (and over the profession); (ii) produce contiguous effects when approach training and profession; (iii) produce control effects on the profession during and after training.